Ground state solutions for a class of Schrödinger–Poisson–Slater equation with Coulomb–Sobolev critical exponent - Jingai Du; Pengfei He; Hongmin Suo (Boundary Value Problems)
Abstract This paper is concerned with the Schrödinger–Poisson–Slater equation involving the Coulomb–Sobolev exponent. We apply the concentration compactness principle and the Pohožaev-type identity to overcome loss of compactness caused by the Coulomb exponent and obtain a ground state solution, which generalizes and improves some recent results in the literature.